Action Research on the Professional Learning Community (PLC) for Chinese Language Transition Between Primary and Secondary Schools in Singapore: 新加坡中小学华文衔接的教师共同体行动研究 - Dong Yan (Mandarinable: Journal of Chinese Studies, 2026)
Based on the demand for the "textbook integration" reform in Singapore's Chinese language education, this study focuses on the transition dilemmas between primary and secondary Chinese teaching. Through a four-year, two-round progressive action research, it explores the role and sustainable development mechanism of cross-stage Teacher Professional Learning Communities. Targeting 28 Chinese teachers from 6 primary and 6 secondary schools in Singapore's S School Cluster, it adopts a mixed research method centred on action research, supplemented by questionnaires, interviews, and case studies, with practices centred on three teaching modules: Life Board/Life Space, Written Interaction, and Oral Interaction. The study finds that the PLC promotes the implementation of teaching integration through a "foundation-laying + in-depth optimization" model, fosters teachers' multi-dimensional professional development, and constructs a sustainable mechanism featuring "integration as the goal, a three-level echelon as the organization, diversified activities as the carrier, and culture, resources, and systems as the three-dimensional support". The research enriches the teacher professional development theory in the context of second language teaching and provides a replicable practical paradigm for the transition of Chinese language education between primary and secondary schools in Singapore.